2007
DOI: 10.1038/sj.ejcn.1602838
|View full text |Cite
|
Sign up to set email alerts
|

Effects of appetite, BMI, food form and flavor on mastication: almonds as a test food

Abstract: Objectives: To investigate the effects of appetitive sensations, body mass index (BMI) and physical/sensory properties of food (almonds) on masticatory indices and resultant pre-swallowing particle sizes. Subjects/Methods: Twelve lean (BMI ¼ 22.270.3) and 12 obese (BMI ¼ 34.370.6) adults. After collecting appetitive ratings, electromyographic recordings were used to assess participants' microstructure of eating for five almond products (raw, dry unsalted roasted, natural sliced, roasted salted and honey roaste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
57
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 52 publications
(72 reference statements)
9
57
0
1
Order By: Relevance
“…Previous research has suggested that the physical form of almonds may influence mastication and pre-swallowing particle size, which could affect the subsequent release of nutrients (Frecka et al, 2008). It is possible that mastication of the whole hazelnuts in the present study produced a pre-swallowing particle size similar to that of ground and sliced hazelnuts, thus eliminating any substantial differences in nutrient availability between nut forms.…”
mentioning
confidence: 66%
“…Previous research has suggested that the physical form of almonds may influence mastication and pre-swallowing particle size, which could affect the subsequent release of nutrients (Frecka et al, 2008). It is possible that mastication of the whole hazelnuts in the present study produced a pre-swallowing particle size similar to that of ground and sliced hazelnuts, thus eliminating any substantial differences in nutrient availability between nut forms.…”
mentioning
confidence: 66%
“…For example, roasting almonds for 6.5 min results in smaller fragments when chewed compared to raw almonds (Varela, Salvador, & Fiszman, 2008). Moreover, the break force of raw almonds is highest followed by that of roasted and sliced almonds (Frecka et al, 2008). When the parenchymal cells are fractured, as compared to simply separated during mastication, the energy and nutrients they contain are more bioaccessible.…”
Section: Orosensory Effects Of Food Formmentioning
confidence: 95%
“…Textural attributes are an example. The perceived brittleness of food may alter chewing responses (Frecka, Hollis, & Mattes, 2008) with subsequent implications for the bioaccessibility of energy and nutrients from the food (Mandalari et al, 2008). Thus, the sensory properties of foods and beverages hold important nutritional implications at multiple levels.…”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of foods have been used to analyze ME, among them natural foods (1,3,8,17) and artificial materials based on silicone (20,21). The subject is instructed not to swallow the material after trituration and the material is collected, passed through graded sieves and weighed.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, natural foods are used in the ME test and the final product resulting from trituration is analyzed with the aid of sieves (1). The inconveniences of this procedure are variations of the food in question and partial food loss (2,3). ME can also be determined by colorimetry (4) using artificial test material whose standardization leads to more reliable result 5,6).…”
Section: Introductionmentioning
confidence: 99%